Lucidin from Rubia cordifolia Outperforms FDA-Approved Lapatinib as a Potential Multitargeted Candidate for Breast Cancer Signalling Proteins - Akram Ahmed Aloqbi; Hadil Alahdal; Amany I. Alqosaibi; Mashael M. Alnamshan; Ibtesam S. Al-Dhuayan; Ahood A. Al-Eidan; Hind A. S. Alzahrani; Nouf K. ALaqeel; Fatmah Hazza Alsharif; Abeer Al Tuwaijri (Pharmaceuticals, 2025)
Background: Breast cancer remains a significant global health concern, with approximately 2.3 million diagnosed cases and 670,000 deaths annually. Current targeted therapies face challenges such as resistance and adverse side effects. This study aimed to explore natural compounds as potential multitargeted breast cancer therapeutics, focusing on Lucidin, an anthraquinone derived from Rubia cordifolia, and comparing its efficacy with Lapatinib, an FDA-approved drug. Methods: We performed multitargeted molecular docking studies on key breast cancer proteins using a natural compound library from ZINC. Comparative analyses of Lucidin and Lapatinib included molecular interaction fingerprints, pharmacokinetics, WaterMap computations (5 ns) to assess water thermodynamics and binding interactions, and Molecular Dynamics Simulations (100 ns) in water to evaluate complex stability and dynamic behaviour. Results: Lucidin demonstrated significant binding affinity and interaction potential with multiple breast cancer targets, outperforming Lapatinib in stability and binding interactions. WaterMap analysis revealed favourable hydration site energetics for Lucidin, enhancing its efficacy. The multitargeted profile of Lucidin suggests a broader therapeutic approach with potential to overcome resistance and side effects associated with Lapatinib. Conclusions: Lucidin shows promise as a novel, multitargeted anti-breast cancer agent with improved efficacy over Lapatinib. These findings provide a foundation for further in vitro and in vivo validation to develop Lucidin as a potential therapeutic option for breast cancer treatment.